Goethe és az irodalmi önaukció - Hites, Sándor (Studia Litteraria, 2021)
The paper looks at two famous cases when Goethe chose to market his works by offering them for auction: In 1797 it was his epic Hermann und Dorothea, in 1825 the rights for the ‘Edition of the Last Hand’ that he put up for sale in informal bidding processes. First I reconstruct the strategies that Goethe and his publishers followed in these deals (that of a second price or Vickrey-auction in the former, that of a sealed-bid auction in the latter case) as experiments of tackling radical uncertainty and contingency in the market evaluation of literary works. Then I analyze the ambivalences underlying Goethe’s views, both insightful and naïve, obsolete and progressive, “idealist” and “utilitarian”, on the relationship of literature and business in the light of his parallel disdain for literary commerce and the growing importance of economic tropes in his critical writings, especially in his notion of Weltliteratur.